Using T Cell Lymphokines of Hyperimmunized Chickens with Salmonella enteritidis to Protect Neonatal Broiler Chicks Against Infectious Bronchitis Disease - AL-Zuhariy , Mushtaq T.B.; Abdulhasan, D. Sahar; Abdulmaged, SaharHamdi; Shihab, Ihsan M. (International Journal of Poultry Science, 2018)
Objective: The present study was designed to reduce infectious bronchitis virus (IBV) infections in broiler chickens because commercial vaccines are not able to provide absolute protection due to the absence of cross immunity between strains, as well as recurrent genetic mutations of IBV. Salmonella-immune lymphokines (S-ILK) from hyperimmunized birds with Salmonella enteritidis were used to enhance the immune resistance of broiler chicks and to reduce the replication of IBV in infected tissues. Materials and Methods: This study was conducted on 250 one-day-old broiler chicks divided into five groups. All groups were treated on the first day as follows: G1: Injected with 0.5 mL S-ILK intraperitoneally and after 30 min challenged with 0.1 mL IBV (variant 2 isolate), G2: Injected with 0.5 mL salmonella-nonimmune lymphokines (S-NILK) intraperitoneally and after 30 min challenged with 0.1 mL IBV (variant 2 isolate), G3: Only injected with 0.5 mL S -ILK intraperitoneally without challenge with IBV, G4: Only challenged with 0.1 mL IBV (variant 2 isolate) and G5: Not injected and not challenged, considered a negative control group. Results: The results showed a significant increase (p